2019
DOI: 10.1016/j.bbr.2018.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral oxidative metabolism mapping in four genetic mouse models of anxiety and mood disorders

Abstract: The psychopathology of depression is highly complex and the outcome of studies on animal models is divergent. In order to find brain regions that could be metabolically distinctively active across a variety of mouse depression models and to compare the interconnectivity of brain regions of wild-type and such genetically modified mice, histochemical mapping of oxidative metabolism was performed by the measurement of cytochrome oxidase activity. We included mice with the heterozygous knockout of the vesicular gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The difference was that the intrinsic components of susceptibility in CSDS mice were largely dependent on epigenetic factors and early life environment [ 50 , 51 ], and that the BDNF het-Met variant confers a genetic predisposition to stress-related behaviors in response to applied stressors [ 52 ]. Meanwhile, a combined analysis of four genetic mouse models of affective disorders showed that the similarity between these models was highly correlated with regional oxidative metabolism revealed by cytochrome oxidase histochemistry, and different in that the GRi (glucocorticoid receptor) mouse model was characterized by several alterations in oxidative metabolism and altered functional connectivity of the extended amygdala and stress response circuit [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The difference was that the intrinsic components of susceptibility in CSDS mice were largely dependent on epigenetic factors and early life environment [ 50 , 51 ], and that the BDNF het-Met variant confers a genetic predisposition to stress-related behaviors in response to applied stressors [ 52 ]. Meanwhile, a combined analysis of four genetic mouse models of affective disorders showed that the similarity between these models was highly correlated with regional oxidative metabolism revealed by cytochrome oxidase histochemistry, and different in that the GRi (glucocorticoid receptor) mouse model was characterized by several alterations in oxidative metabolism and altered functional connectivity of the extended amygdala and stress response circuit [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Symptom sad mood is closely related to abnormal brain connectivity in depression patients. It induces increased activation of the ventrolateral thalamus nucleus [43], while the abnormality of the ventral thalamus nucleus is the important abnormal brain regions of GRI model mice [44]. Besides depressive symptoms, stress symptom intolerable is the most important factor.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial function as related to brain energy metabolism of limbic regions plays a pivotal role in stress responses, motivation, mood, and anxiety (Filiou and Sandi, 2019;Harro et al, 2011;Mällo et al, 2009;Matrov et al, 2019). In this regard, decreased oxidative metabolic capacity was found in the BLA, LA and BST of MSEW as compared to their SN.…”
Section: Early-life Stress and Cbd Modify Cco Activity And Brain Conn...mentioning
confidence: 99%